(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
2024 was proclaimed by the President of Uzbekistan as the “Year of Support for Youth and Business,” which is closely connected not only with increasing the level of material well-being of people, but also with the growth of their culture and education. The well-being and prosperity of our state largely depends on the level of education of its citizens, the achievement of which is facilitated by the establishment of harmonious forms of communication between participants in the learning process. Communication in the learning process is not limited to the transfer of knowledge, but also performs the function of emotional infection, arousing interest, encouraging activity, etc.